The Impact of the Innovative Knowledge of Customers on Their Recommendation Intentions - Zhang, Fenghua; Zhang, Depeng; Lin, Mengfei (Frontiers in Psychology, 2020)
This paper provides a systematic way to examine the impact of the innovative knowledge of customers on their recommendation intentions from firm design perspective, and investigates the moderating effects of guidance methods and design materials provided combining different aspects of cognitive fit, media richness, and sticky information theories. We use the EQXIU platform, conduct two experiments and find that there are significant differences between the novice customers and expert customers in their recommendation intentions. Experts are more prone to no template materials, while novices are more inclined to use modules and templates. Therefore, to inspire innovation, firms should offer personalized opportunities based on customers’ knowledge levels to enhance their experience. Firms should also design the innovative activities taking into consideration the knowledge levels of their customers. At last, limitations of this study and directions for further research are discussed.